The Adaptability of Life on Earth and the Diversity of Planetary Habitats - Schulze-Makuch, Dirk; Airo, Alessandro; Schirmack, Janosch (Frontiers in Microbiology, 2017)
The evolutionary adaptability of life to extreme environments is astounding given that all life on Earth is based on the same fundamental biochemistry. The range of some physicochemical parameters on Earth exceeds the ability of life to adapt, but stays within the limits of life for other parameters. Certain environmental conditions such as low water availability in hyperarid deserts on Earth seem to be close to the limit of biological activity. A much wider range of environmental parameters is observed on planetary bodies within our Solar System such as Mars or Titan, and presumably even larger outside of our Solar System. Here we review the adaptability of life as we know it, especially regarding temperature, pressure, and water activity. We use then this knowledge to outline the range of possible habitable environments for alien planets and moons and distinguish between a variety of Planetary Environment Types (PETs). Some of these types are present in our Solar System, others are hypothetical. Our schematic categorization of alien habitats is limited to life as we know it, particularly regarding to the use of solvent (water) and energy source (light and chemical compounds).